Evaluation of Ecological Carrying Capacity in Qinghai Province Based on DPSIR-TOPSIS Model - Li Xiaoyong; Jia Haifa; Zhao Wanmei (Shuitu baochi tongbao)
[Objective] The ecological carrying capacity of Qinghai Province and its cities and prefectures were quantitatively measured to reveal its spatial and temporal evolution characteristics, in order to provide a reference for the sustainable development of Qinghai Province. [Methods] The ecological carrying capacity evaluation index system was constructed using the DPSIR model and considering five factors: driving force, pressure, state, impact, and response. The entropy value method was applied to determine the weight coefficients of the indexes. The TOPSIS model and the obstacle degree model were used to measure and analyze the ecological carrying capacity and the impact factors for Qinghai Province and its cities and prefectures from 2008 to 2019. [Results] Ecological carrying capacity of Qinghai Province and its cities and prefectures increased significantly from 2008 to 2019. Ecological carrying capacity of cities and prefectures in Qinghai Province differed spatially, with the two eastern cities having greater carrying capacity than other regions. The main factors influencing ecological carrying capacity in Qinghai Province from 2008 to 2019 have generally undergone a transformation that follows the pattern of social development-environmental pollution-population pressure and economic growth rate. [Conclusion] The ecological carrying capacity of Qinghai Province has increased significantly during 2008—2019, but the ecological situation remains severe. Policies regarding ecological protection should be actively implemented, the speed of social and economic development should be accelerated, and the ecological carrying capacity of cities and prefectures should be comprehensively improved in order to achieve high-quality sustainable development in Qinghai Province.